Innovative technologies and financial mechanisms for their stimulation - Abduraxmon G‘ofurovich Tuychiyev; Botirjon Abduraxmon o‘g‘li Abdug‘ofurov (Science and Education, 2025)
This article examines the role and importance of scientific research in the creation of mechanisms and methods for financing new technologies for sustainable economic development and their implementation, as well as proposals and recommendations for achieving an effective solution to issues aimed at financing and commercializing the transfer of innovations, which is one of the main factors in economic development.